High Resolution for Chemical Shifts and Scalar Coupling Constants: The 2D Real‐Time J‐Upscaled PSYCHE‐DIAG1. Issue 22 (19th October 2018) - Tassoti, Sebastian; Novak, Predrag; Butts, Craig P.; Zangger, Klaus
Abstract: The facile determination of chemical shift and scalar coupling constants in NMR spectra is often prevented by spectral overlap and limited resolution. Here, we present a high‐resolution NMR experiment for the simultaneous detection of both resonance frequencies and coupling patterns even with small J‐values. A PSYCHE‐decoupled DIAG (Pure Shift Yielded by Chirp Excitation‐ DIAGonal) experiment, which resolves chemical shift in the indirect dimension of a 2D experiment is combined with real‐time J‐upscaling in order to visualize small coupling constants that would otherwise be hidden in the linewidth of a regular proton or DIAG spectrum. Abstract : The highest resolution for both chemical shifts and scalar coupling constants can be achieved with the 2D J‐upscaled PSYCHE‐DIAG (Pure Shift Yielded by Chirp Excitation‐ DIAGonal correlation) NMR experiment.